Digital Society Based on Public Civility: an Alternative to Strengthen National Character - Kusnadi Kusnadi; Ary Purwantiningsih; Yos Sudarso (Mahesa Research Center, 2023)
This article aims to discuss a digital society based on public civility referring to a concept in which digital technology is used to strengthen national character and morality. In a digital society, technology has become an integral part of everyday life, and its use influences how we communicate, interact, and obtain information. However, the use of this technology has also raised ethical and moral issues. Therefore, the concept of a digital society based on public civility aims to promote moral and ethical values in the use of digital technology, so that technology can be used to strengthen national character and morality. Some of the principles underlying this concept are Openness. Digital society must be open and transparent in managing and using digital technology. Responsibility, every individual in the digital society must be responsible for their actions and the impact they have on others. Cooperation, collaboration, and cooperation between individuals and groups in digital society must be increased to achieve common goals. Education and awareness about the ethics and morality of using digital technologies must be increased throughout the digital society. The method used in analyzing this problem is a qualitative approach with the literature study method. Literature studies are carried out using various types of library sources, such as scientific journals, books, conference papers, research reports, as well as documents, and other publications. In conducting literature studies, researchers need to select relevant and high-quality sources and collect information in a systematic and structured manner. By strengthening the character and morality of the nation through the concept of a digital society based on public civility, it is hoped that digital society will be more aware of ethical values. and morality in the use of digital technology, and can use it positively and constructively to strengthen the nation's character and morality.